PELAYANAN TERAPI BEKAM PADA ANGGOTA MAJELIS TAKLIM ASY SYIFA BATURAJA - Sujati Ni Ketut; Harsanto D Eka; Saprianto Saprianto; Suryanda Suryanda (Jurnal Abdi Masyarakat Kita, 2021)
Health services are currently growing towards naturalist and herbalist services. Public interest in health services originating from eastern medicine is increasing. Included include Cupping. For nurses, Cupping is part of holistic nursing, which has entered the standard of Nursing intervention. The goal of cupping service is the elderly who complain about non-specific complaints along with the degeneration process in the elderly. Suryanda (2016) reported that the application of cupping in the nursing care of a hypertensive client provides comfort and reduces neck pain complaints to the client. This community service aims to provide direct services to the community (members of the Islamic Boarding School Asy syifa Baturaja) who need cupping therapy servants. Activities in the form of counseling about the disease of the elderly and the benefits of cupping and contra indication cupping. Activities carried out in the even semester of the 2019 budget year. The results of cupping therapy are quite effective in high blood pressure patients. Activity outputs are publications in the online media kabarkite.com and activity videos.